2,3,5,4'-Tetrahydroxystilbene-2-O-β-glucoside Isolated from Polygoni Multiflori Ameliorates the Development of Periodontitis - Yu-Tang Chin; Meng-Ti Hsieh; Chi-Yu Lin; Po-Jan Kuo; Yu-Chen S. H. Yang; Ya-Jung Shih; Hsuan-Yu Lai; Guei-Yun Cheng; Heng-Yuan Tang; Chen-Chen Lee; Sheng-Yang Lee; Ching-Chiung Wang; et al. (Hindawi Limited, 2016)
Periodontitis, a chronic infection by periodontopathic bacteria, induces uncontrolled inflammation, which leads to periodontal tissue destruction. 2,3,5,4'-Tetrahydroxystilbene-2-O-beta-glucoside (THSG), a polyphenol extracted from Polygoni Multiflori, reportedly has anti-inflammatory properties. In this study, we investigated the mechanisms of THSG on the Porphyromonas gingivalis-induced inflammatory responses in human gingival fibroblasts and animal modeling of ligature-induced periodontitis. Human gingival fibroblast cells were treated with lipopolysaccharide (LPS) extracted from P. gingivalis in the presence of resveratrol or THSG to analyze the expression of TNF-α, IL-1β, and IL-6 genes. Increased AMP-activated protein kinase (AMPK) activation and SirT1 expression were induced by THSG. Treatment of THSG decreased the expression of LPS-induced inflammatory cytokines, enhanced AMPK activation, and increased the expression of SirT1. In addition, it suppressed the activation of NF-κB when cells were stimulated with P. gingivalis LPS. The anti-inflammatory effect of THSG and P. Multiflori crude extracts was reproduced in ligature-induced periodontitis animal modeling. In conclusion, THSG inhibited the inflammatory responses of P. gingivalis-stimulated human gingival fibroblasts and ameliorated ligature-induced periodontitis in animal model.